Anatomical alterations: biparietal thinning in antiquity. Review of published cases and a new case - Nicol Rossetti; Roberta Fusco; Arianna Vanni; Francesca Garanzini; Alessandra Mazzucchi; Marta Licata (Anthropological Review)
Cranial anatomical variations, such as biparietal thinning, offer critical insights into the health and living conditions of ancient populations. Despite the presence of extensive archaeological records, biparietal thinning remains a relatively rare and understudied condition. This review aims to synthesize existing bioarchaeological literature on biparietal thinning, addressing its historical prevalence, geographical distribution, and potential etiologies.